Ambrose Bierce's Write it right : the celebrated cynic's language peeves deciphered, appraised, and annotated for 21st-century readers /: the celebrated cynic's language peeves deciphered, appraised, and annotated for 21st-century readers. (2009) - Bierce, Ambrose, 1842-1914?
No abstract available